Gynecologic oncology : current diagnosis and treatment - Shingleton, Hugh M (W.B. Saunders, 1996)
University of Alabama, Birmingham. Textbook on gynecologic cancer for the advanced student. Extensive coverage, including special treatment considerations and techniques, and the fundamentals of radiation and chemotherapy. 79 contributors, 59 U.S.
Keywords: nádory ženských pohlavních orgánů; Genital Neoplasms, Female; gynekologie a porodnictví; patologie; onkologie